Relationship between Malay parents’ socioeconomic status and their involvement in their children’s education at home - Suresh Kumar N Vellymalay, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2013)
The present study focuses on the relationship between parents’ socioeconomic status and parental involvement in their children’s education at home. This study uses eighty students of Malay ethnic origin who are studying in one of the best performance-based National Schools in the state of Kedah, Malaysia as a sample. A questionnaire was used to obtain quantitative data related to the parents’ socio-economic background and their involvement strategies in their children’s education at home. The results indicate that most Malay parents, regardless of their socioeconomic background show a high degree of involvement in most of the parental involvement strategies at home to ensure their children’s educational outcomes. In addition, correlation analysis indicates that the relationship between Malay parents’ socioeconomic status and parental involvement strategies at home is not significant in almost all the strategies adopted by the parents.